New Solitary Wave Solutions for Variants of (3+1)-Dimensional Wazwaz-Benjamin-Bona-Mahony Equations - Rezazadeh, Hadi; Inc, Mustafa; Baleanu, Dumitru (Frontiers in Physics, 2020)
In this work, we suggest a Sardar-subequation method which powerful and efficient, for solving distinct forms of (3+1)-Dimensional Wazwaz-Benjamin-Bona-Mahony ((3+1)-Dimensional WBBM) equations. As a result, some new and more general solitary wave solutions (sws) are obtained including generalized hyperbolic and trigonometric functions. Our results demonstrate the power of the proposed method for the determination of sws of nonlinear evolution equations (NLEs), such as (3+1)-Dimensional WBBM equations which we will study in this work.